Fabrication and evaluation of carbonate apatite granule sponges using fish-derived collagen for advanced synthetic bone substitutes - Keiko Kudoh; Kazuya Akita; Takaharu Kudoh; Naoyuki Fukuda; Yoshihiro Kodama; Natsumi Takamaru; Naito Kurio; Kunio Ishikawa; Youji Miyamoto (Journal of Materials Science: Materials in Medicine)
Abstract Carbonate apatite (CO3Ap) granules have been employed as advanced bone substitutes owing to their capacity to remodel into new natural bone, aligning with the bone remodeling process. Their application spans dental clinical fields in both Japan and the US. Nonetheless, owing to the granular nature of CO3Ap, certain challenges in the application of these materials can arise, such as intraoperative scattering and postoperative migration. To address these issues, we integrated CO3Ap granules with collagen to generate a sponge-like composite. Collagen, typically derived from bovine or porcine sources, is commonly utilized in clinical settings despite the potential for infections, including parasitic zoonosis. For the purposes of this study, we selected fish-derived collagen (FC), which minimizes the risk of zoonotic complications. Compared with CO3Ap-G, the CO3Ap granule/FC composites (CO3Ap-G/FCs) fabricated in this study were characterized by an enhanced handling performance. Bone regeneration ability was assessed by implanting these composites into critical-size defects in rat calvarial bones for 2–4 weeks using CO3Ap-G and FC as controls. Radiographic and histological examinations revealed that the bone-regenerative capacity of CO3Ap-G/FCs was equivalent to that of CO3Ap-G. We accordingly conclude that sponge-like CO3Ap-G/FC composites have potential utility as ideal bone substitutes, in that they can be manipulated with forceps, bent, and cut with scissors, without losing the bone-regenerative properties of CO3Ap-G. Graphical Abstract